MAINTAINING CHILDREN'S LEARNING INTERESTS THROUGH AN ISLAMIC EDUCATIONAL PSYCHOLOGICAL APPROACH - Saiful Akhyar Lubis; Mhd Noor Sitorus; Yusnaili Budianti (Program Studi Pendidikan Agama Islam Fakultas Ilmu Tarbiyah Dan Keguruan UIN Raden Fatah, 2022)
This research aims to examine and describe the urgency of Islamic education psychology in maintaining interest in early childhood learning. This study also intends to study, propose and compare to conclude the understanding of early childhood according to the perspective of Islamic education. This study also intends to examine and present learning barriers and challenges related to maintaining interest in early childhood learning and also aspects of learning that need to be developed through the principles of Islamic education psychology, which are traced through the verses of the Qur'an, the hadiths of the prophet Muhammad SAW., and experts’ opinion in Islamic religious literature. This research is a literature review research with a qualitative approach. The collection of data sources is grouped into primary sources and secondary sources. The sources that were collected thematically were parsed and studied to be compared and drawn conclusions, and presented qualitatively. The results of this study are descriptive descriptions of how the psychology of Islamic education is a very urgent solution to maintain interest in early childhood learning based on an educational curriculum designed through the principles of Islamic educational psychology.